Pengelolaan Perpustakaan Keliling di Kantor Perpustakaan, Arsip, danDokumentasi Kabupaten Pesisir Selatan - Elvina, Raisha; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this study was: (1) describe the management of mobile libraries in the Library of the Office, Archives, and Documentation Pesisir Selatan District; and (2) describeÂ  obstacles encountered in the management of mobile libraries in the library of the Office, Archives, and Documentation Pesisir Selatan District. This research includes descriptive research to obtain the necessary data in this study, the researchers conducted observations and interviews. The researchers conducted observations and interviews to four librarians. Based on the data analysis we can conclude library management process carried out by four stages as follows: (1) operational planning bookmobile not running as it should, (2) organizing the library, in the division of tasks for a mobile library pengoperasionalan not well structured; (3) mobilization activities only performed at the beginning of the mobile library operates, and (4) monitoring conducted library head on employee performance and operational implementation of the mobile library was limited to the submission of a written report to the head of the library esmployees. Keywords: mobile libraries; mobile librarie management